Deformation of coracoacromial ligament during overhead movement as an early indicator of subacromial impingement in elite adolescent badminton players - Wang, S.-H.; Yu, T.-Y.; Lin, Y.-C.; Liao, P.-C.; Tsai, W.-C. (The Physician and Sportsmedicine, 2019)
Objectives: Deformation of the coracoacromial ligament during overhead movement has been linked to shoulder pathologies such as impingement and rotator cuff tear. We, therefore, explored this relationship in a group of elite adolescent badminton players.